Vitamin D Deficiency in Rawalpindi –Islamabad Region - Binish Chaudhary (Journal of Rawalpindi Medical College, 2017)
To assess vitamin – D deficiency in Northern Pakistan in order to provide inputs towards developing effective preventive and remedial strategies. Methods:A total of five thousand six hundred and ninety three (n=5693) adult patients of both genders were screened for serum Vitamin D-3 levels over the period of six years. Results:Mean serum Vitamin D3 levels among males and females were in insufficient range and showed no significant difference (P>0.05). In study population 56.5% (n=3216) of patients were Vitamin D-3 deficient (<20 ng/ml), 18.2% (n=1037) showed insufficient levels (20-30 ng/ml) and 25.3% showed sufficient levels (>30 ng/ml). Significant difference was observed on gender stratification with female population showed higher percentage of deficient levels (79.7%) versus males (20.3%) (p<0.05). Age based stratification also showed significant difference with age groups younger than 50 years showed higher percentage of deficient levels than in patients older than 50 years (P<0.05). Conclusion: There is a high prevalence of vitamin D deficiency in population of Rawalpindi and Islamabad regions